A distribuição de renda e a estrutura da economia brasileira - Toledo, Vicente Alves (2019)
The current economic debate is centered on the existence of evidence in developed countries that the increase in income inequality negatively impacts economic growth. This paper sought to translate this debate into the Brazilian context, by analyzing the relationship between income distribution and the productive activity of the Brazilian economy in 2009. Considering the structure of the recent Brazilian economy through a Social Accounting Matrix, the model was determined of Social Accounting that supported the analyzes of this study. The most relevant results showed that the productive sectors with the greatest potential to impact the product of the economy are the industrial sectors, more specifically, the chemical complex, part of the mineral commodities industry and the oil industry. It was also found that the vast majority of the 55 productive sectors analyzed have the potential to increase income inequality as a result of an increase in their final demands, with only 17 improving income distribution. The results also suggested that a decrease in income inequality in the Brazilian economy stimulates production, but, like any increase in income in the family classes, it does not favor key sectors in the productive structure, which compromises sustained economic growth. Finally, through two simulations carried out, there were positive impacts of government transfers through Bolsa Família on economic growth. The study also revealed that Brazilian exports to China in 2009 generated economic growth, but did not benefit income distribution in Brazil. In short, the analyzes carried out touched on wide-ranging discussions on the economic development of Brazil and on the formulation of economic policy strategies. In particular, this dissertation contributes to the literature through recent evidence on the topic investigated for the Brazilian economy, through an analytical structure that allows dialogue with many other works and an original methodology to identify the relationship of each productive sector with the income distribution.